Atividade leishmanicida de constituintes químicos dos frutos de Garcinia brasiliensis - Pereira, Ivan De Oliveira (2009)
The plants have been used in the treatment and cure of illnesses since the antique. When the men started to use the nature in your service. These plants, due to their chemical and pharmaceutical characteristics, have been studied in order to prove their theoretical medicinal capabilities or to obtain new active components. In this context, the Clusiaceae family is made up of forty nine species that are widely distributed, have been studied. Among these species is the genus Rheedia, also known as Garcinia, which is rich in a wide range of components, such as polyprenylated benzophenones and flavonoids. In this work were obtained the hexanic, ethyl-acetate and ethanolic extracts from pericarp of fruits from Garcinia brasiliensis. After the evaluation of leishmanicidal activity in vitro, the hexanic extract shown the more active, thus, this was fractioned yielding three benzophenones - 7-epi-clusianone, garciniaphenone and guttiferone-a – that were evaluated how their leishmanicidal and toxicity activities. With the intention of to determine a possible mechanism of action, these components were then evaluated of their capacity of to inhibit proteases isolated from amastigote forms of Leishmania, have been the ethyl-acetate extract the more effective. Thus this was fractioned yielding the biflavonoid fukugetin, witch also was evaluated in relation your proteases inhibition capacity, showing results very satisfactory. However, when the ethyl-acetate extract and the fukugetin were evaluated in relation the leishmanicidal activity in vitro, not was find the same effect. With these results, we might realize that the hydrophilic of extracts and molecules evaluated in this study can be an essential factor in the leishmanicidal activity, possible by to make transport difficult of this compounds across the plasmatic membrane.